Business valuation : - Mercer, Z. Christopher (John Wiley & Sons, 2008)
The first book to show why business appraisers do what they do and how valuation concepts are interrelated, Business Valuation: An Integrated Theory, Second Edition provides a concise discussion of the most widely debated valuation topics. Fully revised and updated, it defines and explains valuation in the context of the discounted cash flow and Gordon models, providing the most unified and comprehensive framework for thinking about the sources of valuation premiums and discounts. An excellent basis for understanding and correctly applying modern valuation theory, the Second Edition integrates various valuation concepts to reveal a complete and clear picture of business valuation.